2019
DOI: 10.1097/hp.0000000000000998
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Radiation Risk: The Power of Planned, Persuasive Messaging

Abstract: Every day, health physicists and physicians are expected to communicate effectively with concerned people, but rarely (if ever) are they given training on how to effectively communicate. In an age of social media, this paper presents the relevance of teachings from an ancient Greek philosopher. Aristotle's Rhetoric is still considered one of the most influential works on persuasive messaging. He puts the onus of effective communications on the people with the "true" and "just" information to communicate that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 13 publications
(11 reference statements)
1
33
0
Order By: Relevance
“…The findings in this study suggested that in persuading and guiding people’s participation in telehealth interventions and online health information, a number of key elements reinforced the role of speech, such as the matching of voice and intonation and the use of rhetorical devices. The findings of this study were supported by the previous researchers’ emphasis on the importance of phrasing skills and nonverbal signals/paralanguage (e.g., vocal tones and expressions) during communication [ 74 , 83 ]. Some researchers have noted that expertise accounts for only 15–20% of communicator credibility, while concern and empathy account for approximately 50%.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The findings in this study suggested that in persuading and guiding people’s participation in telehealth interventions and online health information, a number of key elements reinforced the role of speech, such as the matching of voice and intonation and the use of rhetorical devices. The findings of this study were supported by the previous researchers’ emphasis on the importance of phrasing skills and nonverbal signals/paralanguage (e.g., vocal tones and expressions) during communication [ 74 , 83 ]. Some researchers have noted that expertise accounts for only 15–20% of communicator credibility, while concern and empathy account for approximately 50%.…”
Section: Discussionsupporting
confidence: 87%
“…Some researchers have noted that expertise accounts for only 15–20% of communicator credibility, while concern and empathy account for approximately 50%. Empathy can be judged in the first 9–30 s of meeting from the mental aura of the communicator (including dress, hair, posture and facial expressions) [ 83 ]. During verbal communication, the matching of voice and intonation not only helps create emotional resonance between the communicators, but also facilitates the educational content accepted and internalized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using too many technical terms and complicating the narrative may increase confusion and concern in the audience. 19 The ability to accurately and meaningfully communicate radiation risk information to health professionals, patients and carers is of utmost importance as it can influence healthcare pathway decisions. When dose and risk information is not communicated clearly to patients and carers, the consent process can be unnecessarily prolonged, or consent may not be given as the concerns of the patient/carer have not been met.…”
Section: Introductionmentioning
confidence: 99%
“…As concluded by Weider, for effective radiation risk communication we need to personalise communication like we personalise medical diagnosis and treatment. 19 The aim of this study is to contribute to the knowledge base regarding paediatric diagnostic nuclear medicine and PET/MR procedures and provide a standardised approach for the communication of radiation dose and associated risk at RCH. The standardised information can then be personalised by health professionals as required (e.g.…”
Section: Introductionmentioning
confidence: 99%